2019
DOI: 10.1111/jep.13282
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for implementing shared decision making in elective surgery by health care practitioners: A systematic review

Abstract: Rationale, Aims and Objectives To summarize relevant international scientific evidence on strategies aimed at facilitating or improving health care practitioners' adoption of shared decision making in elective surgery. The review evaluated the effectiveness of these strategies and described the characteristics of identified strategies. Method A systematic search of the literature was conducted up to March 2019. The review included interventions that targeted patients, health care practitioners, or health syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Benefits from these types of analyses include support of decision aids and shared decision making to enable the patient to know what they can expect following surgery [ 28 ]. For example, the same review as discussed above identified a 5.7% chance of deep surgical site infection following revision hip replacement surgery, as shown in Fig.…”
Section: Main Bodymentioning
confidence: 99%
“…Benefits from these types of analyses include support of decision aids and shared decision making to enable the patient to know what they can expect following surgery [ 28 ]. For example, the same review as discussed above identified a 5.7% chance of deep surgical site infection following revision hip replacement surgery, as shown in Fig.…”
Section: Main Bodymentioning
confidence: 99%
“…Although the performance media (i.e., photos, texts, and videos) of the Internet platform are different, the forms of performance are almost the same (Jennifer et al, 2020;Yuan et al, 2020). Participants can interact with the works by means of reviewers, bullet-screen comments, and favoriting, while with some artistic interactions (Hearn and Hearn, 2020;Vinken and Upadhye, 2020;Clarabelle et al, 2021). There are also art activities taking online and offline interactions simultaneously with specific processes, using the Internet for publicity while holding offline activities.…”
Section: Influencing Factors Of Social Network Based On the Questionnaire Surveymentioning
confidence: 99%
“…They have highlighted the importance of embedding SDM within the clinical work ow, importance of staff understanding the purpose and effect of SDM strategies, the need for clinical champions, a team-based organisational culture and positive social and implementation supports. [10,11] An analysis of SDM in aged care also highlighted capacity and organisational readiness as important. [12] However, very few studies have used a theoretical foundation to drive the process of implementing SDM in clinical practice, [13] despite theory being important for overcoming implementation barriers and providing structure for evaluation.…”
Section: Introductionmentioning
confidence: 99%